2023
DOI: 10.3390/vaccines11050999
|View full text |Cite
|
Sign up to set email alerts
|

A First-in-Human Trial to Evaluate the Safety and Immunogenicity of a G Protein-Based Recombinant Respiratory Syncytial Virus Vaccine in Healthy Adults 18–45 Years of Age

Abstract: Background: With the enormous morbidity and mortality caused by respiratory syncytial virus (RSV) infections among infants and the elderly, vaccines against RSV infections are in large market demand. Methods: We conducted a first-in-human (FIH), randomized, double-blind, placebo-controlled dose escalation study to evaluate the safety and immunogenicity response of the rRSV vaccine (BARS13) in healthy adults aged 18–45. A total of 60 eligible participants were randomly assigned to receive one of four dose level… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Several vaccine approaches based on RSV G have been investigated, utilizing the CCD as a stand-alone antigen or as an add-on component, co-formulated with an RSV F vaccine [ 21 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. Multiple strategies have been explored to overcome the limited immunogenicity of the CCD peptide, including multimerization of short peptides and display on synthetic, as well as self-assembling nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…Several vaccine approaches based on RSV G have been investigated, utilizing the CCD as a stand-alone antigen or as an add-on component, co-formulated with an RSV F vaccine [ 21 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. Multiple strategies have been explored to overcome the limited immunogenicity of the CCD peptide, including multimerization of short peptides and display on synthetic, as well as self-assembling nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple vaccine platforms are being developed for RSV vaccination and for various target groups [ 87 ]. Virus-like particle-based vaccines [ 69 ], mRNA-based vaccines [ 70 , 71 ], G protein-based recombinant vaccines [ 72 ], Mycobacterium bovis BCG-based recombinant vaccines [ 73 ], adenovirus vector-based vaccines [ 74 , 75 , 76 ] (development has been halted by its manufacturer in March 2023 after portfolio review), and Modified Vaccinia Ankara (MVA) poxvirus-based recombinant vaccines [ 78 ] have been immunogenic and well-tolerated in early trials in healthy participants. Beyond the trials in healthy participants, although a large multinational trial of RSV fusion protein nanoparticle vaccine did not reach its desired efficacy outcome [ 80 ], other platforms involving adenovirus vector-based vaccines [ 81 , 82 , 84 ] and mRNA-based vaccines appear more promising.…”
Section: Discussionmentioning
confidence: 99%
“…BARS13, manufactured by Advaccine Biopharmaceuticals Co., uses the RSV-G protein as the antigen, co-administered with cyclosporine A as the adjuvant [59,60]. Evaluation of the vaccine in younger adults aged 18-45 years in a Phase I clinical trial (NCT04851977) revealed a dose-dependent induction of immunity regarding specific antibodies against the RSV-G protein [59]. Subsequently, a Phase II study (NCT04681833) followed to assess the vaccine in older adults aged 60-80 years.…”
Section: Bars13 (Adv110)mentioning
confidence: 99%